Microplastic contamination in pelagic fishes from the east coast of Peninsular Malaysia - Nawawi, Ain Waznin Nuha Ahmad; Ezraneti, Riri; Miskon, Mohd Fuad; Mohamed, Juliana (Universitas Malikussaleh, 2025)
Microplastic contamination in marine environments is a growing concern, particularly in fish species consumed by humans. This study investigates the presence and characteristics of microplastics in the livers of Indian mackerel (Rastrelliger kanagurta) and yellowtail scad (Atule mate) collected from Pahang and Kelantan. The abundance of microplastics was quantified for each species at each location, with the total count normalized by the number of fish analyzed following the extraction and identification process. Microplastic identification was conducted using a Stereoscopic Microscope, while polymer composition was determined through ATR-FTIR spectroscopy. The microplastic abundance recorded was 0.067 particles per fish. The microplastic identified were predominantly fragments and filaments in red, black, and grey colors. The polymers found were poly(diallyl phthalate) (PDAP), poly(butylene terephthalate) (PBT), polypropylene (PP), poly(cyclohexylenedimethylene terephthalate) (PCT), and high-density polyethylene (HDPE). The finding of microplastics in fish livers provides preliminary evidence of contamination and suggests direct exposure of these vital organs. This raises serious concerns about potential contamination in other crucial organs, including the gills, gastrointestinal tract, tissues, and even the brain. This highlights the need for further research on microplastic exposure pathways and its ecological implications along the east coast of Peninsular Malaysia.